Genetic Diversity of Cinnamomum porrectum (Roxb.) Kosterm. in Southern Thailand Detected by Inter Simple Sequence Repeat (ISSR) Analysis - Uthairatsamee , Suwimon; Pipatwattanakul, Damrong (วารสารวนศาสตร์ไทย, 2022)
Genetic diversity of Cinnamomum porrectum (Roxb.) Kosterm. (‘Thep tharo’) in southern Thailand was assessed by analyzing molecular genetic markers at the population level. Inter simple sequence repeat (ISSR) markers were used to analyze the genetic diversity of six populations in Phangnga, Phuket, Phatthalung, Satun, Krabi, and Songkhla provinces. In total, 73 amplified bands were obtained from 117 individuals of all sampled populations using seven primers. At the species level, the percentage of polymorphic loci (P), the mean expected heterozygosity (He), and the Shannon’s information index of diversity (I) were high (87.67%, 0.2883, and 0.4343, respectively). However, P, He, and I were relatively low at the population level with averages of 47.03%, 0.1689, and 0.2508, respectively. Among the six populations investigated, the Songkhla and Phangnga populations revealed the highest genetic diversity, followed by Satun, Phatthalung, Phuket and Krabi populations, respectively. Based on Nei’s genetic differentiation (Gst) value, 35.51% of genetic differentiation existed among populations. The gene flow (Nm) was 0.9081. UPGMA cluster analysis divided the populations into two main groups. One consisted of the populations of Satun, Songkhla, Phangnga, and Phatthalung, while the other was composed of the Phuket and Krabi populations. Based on the results of the present study and field survey, it could be suggested that in situ gene conservation is very important for this species, especially in the Songkhla and Phangnga populations due to their higher genetic diversity and larger population sizes. At the same time, ex situ gene conservation should be established as an option to conserve the genetic material of the Satun, Phatthalung, Phuket, and Krabi populations that showed low genetic diversity and small population sizes. Keywords: Cinnamomum porrectum, ‘Thep tharo’, genetic diversity, ISSR, conservation